223k views
4 votes
Subtract (7x-2) - (3x-5)

User Tinamarie
by
5.7k points

2 Answers

3 votes

Answer:

4x + 3 is the answer obtained when we subtract (7x-2) - (3x-5)

Explanation:

Given that, (7x-2)-(3x-5)

Minuend = 7x-2

Subtrahend = 3x-5

In subtraction of algebraic terms, we place the variables together and the constants together and then perform the operation

Thus,

= (7x-2)-(3x+5) opening brackets and rewrite the equation.

= 7x-2-3x+5 bring 'x' terms together

= (7x-3x)-(2-5)

= 4x-(-3)

= 4x+3

Thus, after subtracting (7x-2)-(3x-5) we get 4x+3

User Indra
by
4.9k points
3 votes

Answer:

4x - 3

Explanation:

(7x - 2) - (3x - 5)

Open the bracket and observe the signs,

7x -2 - 3x + 5 ( when the minus outside the bracket multiplies minus in the bracket, it becomes plus)

Collect like terms

7x - 3x - 2 + 5

4x - 3

User Deni Spasovski
by
5.8k points